2022
DOI: 10.5194/gmd-15-5045-2022
|View full text |Cite
|
Sign up to set email alerts
|

SnowClim v1.0: high-resolution snow model and data for the western United States

Abstract: Abstract. Seasonal snowpack dynamics shape the biophysical and societal characteristics of many global regions. However, snowpack accumulation and duration have generally declined in recent decades, largely due to anthropogenic climate change. Mechanistic understanding of snowpack spatiotemporal heterogeneity and climate change impacts will benefit from snow data products that are based on physical principles, simulated at high spatial resolution, and cover large geographic domains. Most existing datasets do n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…In the Rocky Mountains, elevated temperatures have reduced soil moisture availability through declining snowpack and early snowmelt (Rangwala et al ., 2012; Pepin et al ., 2015; Fyfe et al ., 2017). The timing of snowmelt will continue to accelerate under projected climate scenarios (Lute et al ., 2022), exposing B. stricta and other montane species to heightened drought stress. A glasshouse experiment demonstrated that drought stress depresses fecundity in high‐elevation accessions of B. stricta (MacTavish & Anderson, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the Rocky Mountains, elevated temperatures have reduced soil moisture availability through declining snowpack and early snowmelt (Rangwala et al ., 2012; Pepin et al ., 2015; Fyfe et al ., 2017). The timing of snowmelt will continue to accelerate under projected climate scenarios (Lute et al ., 2022), exposing B. stricta and other montane species to heightened drought stress. A glasshouse experiment demonstrated that drought stress depresses fecundity in high‐elevation accessions of B. stricta (MacTavish & Anderson, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The black lines show daily mean temperatures across blocks, with dashed horizontal lines at 0°C. I have indicated the observed snowmelt date in each site along with end‐of‐century projections under Representative Concentration Pathway 8.5 (Lute et al, 2022). (B) Models project continued reductions in snowpack under climate change (Lute et al, 2022), which could reduce the duration of winter chilling and delay spring phenological events, such as germination, leaf‐out, and flowering.…”
Section: Insufficient Overwinter Chillingmentioning
confidence: 99%
“…I have indicated the observed snowmelt date in each site along with end‐of‐century projections under Representative Concentration Pathway 8.5 (Lute et al, 2022). (B) Models project continued reductions in snowpack under climate change (Lute et al, 2022), which could reduce the duration of winter chilling and delay spring phenological events, such as germination, leaf‐out, and flowering. Although many species have advanced the timing of spring events in response to climate change, accelerated phenology is not a universal response to early springs (Yu et al, 2010).…”
Section: Insufficient Overwinter Chillingmentioning
confidence: 99%